Analysis of Factors Affecting Student Satisfaction with the Implementation of Hybrid Learning in the Faculty of Economics and Business, UNJ - Risqi Adelia, Divania; Eka Dewi Utari,; Marsofiyati, (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study investigates the determinants of student satisfaction in the implementation of hybrid learning at the Faculty of Economics and Business, Universitas Negeri Jakarta (FEB UNJ). Using a quantitative approach, data were gathered from 80 undergraduate students who participated in hybrid learning. The study employed descriptive statistics, validity and reliability testing, classical assumption testing, and multiple linear regression analysis with SPSS. The findings reveal that service quality, ease of technology use, and learning effectiveness significantly affect student satisfaction, with learning effectiveness emerging as the most dominant factor. These results highlight the need for balanced integration between technological accessibility, quality academic services, and pedagogical effectiveness to optimize hybrid learning outcomes in higher education.